Vision Loss after Intravitreal Injection of Autologous “Stem Cells” for AMD - Kuriyan, Ajay E; Albini, Thomas A; Townsend, Justin H; Rodriguez, Marianeli; Pandya, Hemang K; Leonard, Robert E; Parrott, M. Brandon; Rosenfeld, Philip J; Flynn, Harry W; Goldberg, Jeffrey L (The New England journal of medicine, 2017)
In three women with age-related macular degeneration and with visual acuity ranging from 20/30 to 20/200 before they received bilateral intravitreal injection of autologous “stem cells,” blinding complications developed in each of their eyes. Age-related macular degeneration (AMD) is the leading cause of vision loss in persons older than 75 years of age in the United States. 1 Progressive dysfunction and loss of retinal pigment epithelium cells and photoreceptors lead to poor visual acuity in patients with non-neovascular AMD. 2 The potential role of delivering subretinal human retinal pigment epithelium, photoreceptor cells, or both, differentiated from pluripotent stem cells, to replace the damaged cells in patients with non-neovascular AMD is being investigated in several clinical trials registered by the Food and Drug Administration (FDA) and approved by institutional review boards. 3 As of November 2, 2016, at . . .